Reducing depressive or anxiety symptoms in post-stroke patients: Pilot trial of a constructive integrative psychosocial intervention - Fang, Yihong; Mpofu, Elias; Athanasou, James (International Journal of Health Sciences, 2017)
Background: About 30% of stroke survivors clinically have depressive symptoms at some point following stroke and anxiety prevalence is around 20-25%. Objective: The purpose of this brief report is to evaluate a pilot trial of a constructive integrative psychosocial intervention (CIPI) over standard care in post-stroke depression or anxiety. Methods: Patients were randomly assigned to either CIPI (n = 23) or standard care (n = 19). Patients were assessed using the Hospital Anxiety and Depression Scale at the 1st, 3rd, and 6th months to monitor changes of mood. Results: A Wilcoxon signed-rank test indicated that compared to admission baseline, patients with the intervention had significantly normal post-stroke depression symptom levels at the 1st, 3rd, and 6th months (P < 0.005). Conclusion: CIPI appears to be of incremental value in treating depression as well as anxiety in subacute care.